Breast Cancer in Young Women in Latin America: An Unmet, Growing Burden. (25th November 2013) - Villarreal‐Garza, Cynthia; Aguila, Christian; Magallanes‐Hoyos, Maria C.; Mohar, Alejandro; Bargalló, Enrique; Meneses, Abelardo; Cazap, Eduardo; Gomez, Henry; López‐Carrillo, Lizbeth; Chávarri‐Guerra, Yanin; Murillo, Raúl; Barrios, Carlos
Abstract : Background: Breast cancer (BC) is the leading cause of malignancy‐related deaths among women aged ≤45 years. There are unexplored and uncertain issues for BC in this particular group in Latin America. The aim of this study is to evaluate BC incidence and mortality among young women and related clinicopathological and survivorship aspects in this region. Materials and Methods: Data were obtained from Globocan 2008 and the International Agency for Research on Cancer's Cancer Incidence in Five Continents series plus databases. We requested collaboration from the 12 different national cancer institutes in Latin America through SLACOM, the Latin American and Caribbean Society of Medical Oncology, and conducted a systematic literature review to obtain local data regarding the prevalence of BC among young women and their characteristics, outcomes, and survivorship‐related issues. Results: BC incidence and mortality proportions for Latin American women aged <44 years were higher when compared with those of developed countries (20% vs. 12% and 14% vs. 7%, respectively). We found only a few Latin American series addressing this topic, and prevalence varied between 8% and 14%. Stage II and III disease, high histological grade, and triple‐negative and HER2 BC were features frequently observed among young Latin American BC patients. Conclusion: The rising incidence and mortality of BC in young Latin American women is a call to action in the region. It is necessary to monitor the epidemiological and clinical data through reliable cancer registries and to consider the implementation of protocols for education of patients and health professionals. This unmet, growing burden must be considered as a top priority of the national programs in the fight against BC, and models of specialized units should be implemented for this particular group of patients to provide better care for this emergent challenge. Abstract : The aim of this study was to evaluate breast cancer (BC) incidence and mortality among young Latin American women and related clinico‐pathology and survivorship. Incidence and mortality of BC are rising among this population. The resulting burden must be considered as a top priority of national programs in the fight against BC.